2017
DOI: 10.1038/s41598-017-01075-x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional selection predicts rapid automatized naming ability in Chinese-speaking children with ADHD

Abstract: Children with attention-deficit/hyperactivity disorder (ADHD) are reported to have a significantly higher risk of showing reading difficulties or disorders. Here, we aimed to identify the relationship between electroencephalographic (EEG) marker of spatial attention and reading ability in Chinese children with ADHD. First, we demonstrated that rapid automatized naming (RAN) is a strong predictor of reading ability in Chinese-speaking children. Then, EEG data of 9-to 15-year-old children with ADHD (n = 38) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Other studies have further shown that attention deficit factors (e.g. attentional selection, spatial attention) influence processing speed/naming speed tasks (Shanahan et al., 2006; Ryan et al., 2017; Wang et al., 2017). Furthermore, our findings show that attention networks were more strongly affected by executive control, which could also predict naming speed.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have further shown that attention deficit factors (e.g. attentional selection, spatial attention) influence processing speed/naming speed tasks (Shanahan et al., 2006; Ryan et al., 2017; Wang et al., 2017). Furthermore, our findings show that attention networks were more strongly affected by executive control, which could also predict naming speed.…”
Section: Discussionmentioning
confidence: 94%
“…[54][55][56] Research has shown a relationship between attention deficits and speeded naming tasks, including object, color, and number naming, and attention deficit affects processing speed and naming speed tasks. [57][58][59][60][61] We suggest that this is because of the overlap between the DMN and the ventral attention network (VAN) of the right posterior IFG, which may lead to task-related coupling in this control system. [62,63] Specifically, the involvement of the VAN may help monitor the transition between perception and action to support appropriate behavior, such as suppressing motor responses in the presence of heightened response competition.…”
Section: Discussionmentioning
confidence: 97%
“…Optic ataxia was assessed using the method described by Karnath and Perenin ( 2005 ). Visuospatial function was assessed by the revised Rey-Osterrieth Complex Figure Test, and a rapid automatized naming test was used to examine reading ability (Shin et al, 2006 ; Wang et al, 2017 ). Additionally, facial agnosia was evaluated by accurately naming ten celebrities (including national leaders and actors) based on images.…”
Section: Methodsmentioning
confidence: 99%